ПРАВО НА ОБРАЗОВАНИЕ: ГОСУДАРСТВЕННАЯ ПОЛИТИКА РЕСПУБЛИКИ МОЛДОВА ПО ОБЕСПЕЧЕНИЮ ДОСТУПА ДЕТЕЙ С ОГРАНИЧЕННЫМИ ВОЗМОЖНОСТЯМИ К КАЧЕСТВЕННОМУ ОБРАЗОВАНИЮ - Боршевский, Андрей Петрович, Сосна Борис Ильич (SUPREMANCE OF LAW, 2016)
Right to Education: State policy of the Republic of Moldova to ensure the access of children with disabilities to quality education. Phis article focuses on public policy in the Republic of Moldova to ensure the access of children with disabilities to quality education. This article is funded by the European Union. Opinions expressed in the article do not necessarily represent those of the European Union.